Cutaneous Manifestations of Thyroid Hormone Disorder - Karuna Singh Sijapati; Arpana Rijal; Sudha Agrawal; Dhan Keshar Khadka; Robin Maskey (Nepal Journal of Dermatology, Venereology & Leprology)
Introduction: Thyroid hormone disorder (THD), a major health problem, is associated with a wide range of diseases. One of the organs, which  shows this wide range of clinical signs is the skin. Some dermatological findings may be the first symptoms of THD. Therefore, this study was planned to determine various cutaneous manifestations of THD that can be used as a diagnostic marker for THD. In Nepal due to lack of awareness, thyroid diseases may go unnoticed .So, cutaneous manifestations help in early diagnosis and treatment of THD.